The evolution, variation, and expression patterns under development and stress responses of the NAC gene family in the barley pan-genome - Liu, Xin; Zhang, Minghu; Su, Jian; Wu, Lei; Shen, Mang; Zhuang, Yamei; Wang, Qi; Chen, Gang (Frontiers in Plant Science, 2025)
The NAC transcription factor family is pivotal in regulating plant development and stress responses, yet its diversity and evolutionary dynamics in barley (Hordeum vulgare) remain underexplored. In this study, we performed a comprehensive pan-genome analysis to identify and characterize the HvNACs across 20 barley accessions. A ranging from 127 to 149 HvNACs were identified in each genome, in which the Morex genome harbored the highest count. These HvNACs were classified into 201 orthogroups, further stratified into core (102), soft-core (18), shell (25), and lineage-specific (56) categories. Phylogenetic analysis delineated them into 12 subfamilies, of which the core genes have undergone strong purifying selection, by contrast, the shell and lineage-specific genes were under relaxed selection constraint, suggesting functional diversification in barley. Genomic variation, such as PAVs and CNVs, largely driven by TEs, highlighted the dynamic nature of NAC loci. Furthermore, transcriptome profiling of the HvNACs demonstrated diverse tissue expression patterns and different response characteristics under salt stress. These findings elucidate the evolutionary and functional dynamics of HvNACs, offering valuable insights for genetic improvement of breeding programs in barley as well as in other crops.